2019
DOI: 10.7567/1347-4065/ab4614
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gas composition on surface sterilization by using LF-microwave hybrid plasma source

Abstract: A new type of atmospheric-pressure non-thermal plasma source was developed by a combining a low-frequency (LF) plasma jet with microwave plasma as a hybrid plasma. The LF-microwave hybrid plasma has a large amount of reactive species compared to conventional LF plasma jet owing to higher-energy electrons, which are accelerated by the oscillating electric fields of the microwave. Moreover, it can be sustained stably at a higher composition rate of the process gas in the discharge gas. The objective of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…The LF-microwave hybrid plasma source is composed of a rectangular waveguide (WRJ-2), which contains a cylindrical slotted antenna surrounding a discharge quartz tube, and a cylindrical copper electrode, which is installed in the discharge quartz tube. [27][28][29] Two slits are arranged on the cylindrical slotted antenna. The frequency of the microwave was 2.45 GHz and the power could be increased up to 2 kW.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The LF-microwave hybrid plasma source is composed of a rectangular waveguide (WRJ-2), which contains a cylindrical slotted antenna surrounding a discharge quartz tube, and a cylindrical copper electrode, which is installed in the discharge quartz tube. [27][28][29] Two slits are arranged on the cylindrical slotted antenna. The frequency of the microwave was 2.45 GHz and the power could be increased up to 2 kW.…”
Section: Methodsmentioning
confidence: 99%
“…A short plunger was installed for impedance matching between the plasma and the microwave circuit, and the forward, reflected powers were measured by using a directional coupler with power meters. [27][28][29] The flow rate of each gas was adjusted by each gas-flow controller. The LF plasma jet was generated at the beginning of the operation by applying an LF high voltage to a cylindrical copper electrode in the discharge quartz tube.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that the plasma had a significant bactericidal effect [21]. Shintani et al found that the primary cause of nitrogen plasma sterilization was the active particle ONOO − [22], and Tonmitr et al investigated the effect of different working gases on bactericidal efficacy [23]. Nguyen et al reported a plasma-based nanomaterial that promotes apoptosis of cancer cells [24].…”
Section: Introductionmentioning
confidence: 99%